2006
DOI: 10.1016/j.puhe.2006.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of social marketing interventions for health improvement: What's the evidence?

Abstract: Methodology/Approach: Review of systematic reviews and primary studies using prespecified search and inclusion criteria. Social marketing interventions were defined as those which adopted specified social marketing principles in their development and implementation.Findings: A total of 54 interventions met the inclusion criteria. There was evidence that interventions adopting social marketing principles could be effective across a range of behaviours, with a range of target groups, in different settings, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
242
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(260 citation statements)
references
References 29 publications
10
242
0
5
Order By: Relevance
“…Reviews that examined the eff ects of social marketing showed positive eff ects on promotion of awareness and use of insecticide-treated nets 23 and adop tion of recom mended practices for dengue pre vention. 24 However, the studies examined were of low quality.…”
Section: Social Marketingmentioning
confidence: 99%
“…Reviews that examined the eff ects of social marketing showed positive eff ects on promotion of awareness and use of insecticide-treated nets 23 and adop tion of recom mended practices for dengue pre vention. 24 However, the studies examined were of low quality.…”
Section: Social Marketingmentioning
confidence: 99%
“…Providing effective communication materials is not as easy as it sounds and is unlikely to 223 bring about behaviour change in isolation although it is often a pre-requisite to more intensive of public health behaviours (40) . In the UK the Change 4 Life programme engages the public to 230 encourage them to look at their diet and levels of physical activity and make changes to 231 improve their health (41) .…”
Section: Social Marketing and Information Provision 222mentioning
confidence: 99%
“…In the UK, sugar cane was imported from around 1300 and sugar beet in the 1700s but it was 39 the automation of the process of extracting sugars in the 1900s that brought about huge 40 change. Development into a modern and efficient sector led to sugar becoming cheap and 41 plentiful from that time (1) and sugar consumption grew exponentially.…”
mentioning
confidence: 99%
“…732,802,853,872,[1142][1143][1144][1145] McGuckin and colleagues reported an increase in hand hygiene compliance and alcohol-based hand rub use by using "authority figures" as role models for empowerment. 853 The medical director, nurse manager, director of nursing, and infection control professional dedicated to the medical/surgical ICU recorded short audio messages about hand hygiene, such as "we want 100% compliance with hand hygiene in our ICU" and "remember to use sanitizer", that were broadcast at randomly timed intervals from the announcement speakers at the nurses' station.…”
Section: Role Modellingmentioning
confidence: 99%